2010
DOI: 10.1038/onc.2010.438
|View full text |Cite
|
Sign up to set email alerts
|

WW domain-mediated interaction with Wbp2 is important for the oncogenic property of TAZ

Abstract: The transcriptional co-activators YAP and TAZ are downstream targets inhibited by the Hippo tumor suppressor pathway. YAP and TAZ both possess WW domains, which are important protein–protein interaction modules that mediate interaction with proline-rich motifs, most commonly PPXY. The WW domains of YAP have complex regulatory roles as exemplified by recent reports showing that they can positively or negatively influence YAP activity in a cell and context-specific manner. In this study, we show that the WW doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 41 publications
4
118
0
Order By: Relevance
“…S3A). Cluster 1 validated previously reported interactions for YAP1 or TAZ, which include PPP1CA (51), WBP2 (52), and TP53BP2 (53). Several uncharacterized preys in this cluster, such as CCDC85C and C9orf140, were considered as potential regulators of YAP1 or TAZ.…”
Section: Overview Of the Interaction Network In The Human Hipposupporting
confidence: 73%
“…S3A). Cluster 1 validated previously reported interactions for YAP1 or TAZ, which include PPP1CA (51), WBP2 (52), and TP53BP2 (53). Several uncharacterized preys in this cluster, such as CCDC85C and C9orf140, were considered as potential regulators of YAP1 or TAZ.…”
Section: Overview Of the Interaction Network In The Human Hipposupporting
confidence: 73%
“…TAZ overexpression can induce epithelial cells to undergo EMT, which is associated with tumor metastasis. Moreover, TAZ expression induces oncogenic transformation in NIH3T3 cells in vitro (37). It has been reported that TAZ protein levels are elevated in human cancers (15).…”
Section: Discussionmentioning
confidence: 98%
“…To identify candidate transcriptional regulatory proteins that interact with the WW domains of Yki and its mammalian homologues, YAP and TAZ, we performed large-scale immunoprecipitations with TAZ in cultured cells. 24 A major interaction partner of TAZ was WBP2, homologues of which are found in many different species including D. melanogaster, which has a sole WBP2 homologue, CG11009 (hereafter referred to as Wbp2). The wbp2 gene is predicted to encode for two polypeptides of 337 and 427 amino acids, each of which contains a GRAM (glucosyltransferases, Rab-like GTPase activators and myotubularins) domain that has no defined function and two evolutionarily conserved P-P-X-Y (PY) motifs ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…24 This analysis revealed a specific interaction with WW domainbinding protein-2 (WBP2). Interestingly, WBP2 was one of the first identified YAP-interacting proteins 25 and was previously shown to cooperate with YAP to increase ligand-dependent transactivation of oestrogen and progesterone receptors.…”
mentioning
confidence: 99%